Impact of postdischarge care fragmentation on clinical outcomes and survival following transcatheter aortic valve replacement - KARAÇÖP, ERDEM; KARAÇÖP, ERDEM; ENHOŞ, Asim; ENHOŞ, ASIM; Bakhshaliyev, NIJAD; BAKHSALIYEV, NIJAD (My University, 2020)
Background. The study aimed to evaluate the prognostic impact of postdischarge care fragmentation in patients undergoing transcatheter aortic valve replacement (TAVR). Methods. A total of 266 patients undergoing TAVR due to severe aortic stenosis were included in this retrospective cohort study. Patients were assigned to one of two groups based on presence (n= 104) and absence (n= 162) of postdischarge care fragmentation. Fragmented care was defined as at least one readmission to a site other than the implanting TAVR center within 90 days. Prognostic impact of care fragmentation on clinical outcomes and predictors of long-term mortality were investigated.